ANALYSIS OF OBSTACLES FACED BY FOURTH GRADE ELEMENTARY SCHOOL STUDENTS IN UNDERSTANDING INSTRUCTIONS IN ENGLISH AND EFFORTS TO OVERCOME THEM AT SDN 060878 KRAKATAU MEDAN TIMUR - Eva Betty Simanjuntak; Grace sio naro Sitanggang; Ines Situmorang; Sihole Anatasya Pesta Natalia; Suci Hardiyanti (PT. Jurnal Center Indonesia Publisher, 2025)
This study investigates the difficulties faced by fourth-grade students at SDN 060878 Krakatau Medan Timur in understanding English classroom instructions. The research identifies four main obstacles: limited vocabulary mastery, low confidence and motivation, less varied teaching strategies, and minimal English exposure outside school. The study also highlights effective teacher efforts such as repeating instructions, providing bilingual explanations, using demonstrations, and implementing interactive activities. These findings are expected to guide teachers in creating more adaptive and supportive instructional practices in elementary English learning.